Impairment of mitophagy and autophagy accompanies calcific aortic valve stenosis favouring cell death and the severity of disease . Issue 11 (10th August 2021) - Morciano, Giampaolo; Patergnani, Simone; Pedriali, Gaia; Cimaglia, Paolo; Mikus, Elisa; Calvi, Simone; Albertini, Alberto; Giorgi, Carlotta; Campo, Gianluca; Ferrari, Roberto; Pinton, Paolo
Abstract: Aims: In the last 15 years, some observations tried to shed light on the dysregulation of the cellular self-digestion process in calcific aortic valve stenosis (CAVS), but the results obtained remain still controversial. This work is aimed to definitively establish the trend of autophagy in patients affected by CAVS, to analyse the putative involvement of other determinants, which impact on the mitochondrial quality control mechanisms and to explore possible avenues for pharmacological interventions in the treatment of CAVS. Methods and results: This observational study, performed exclusively in ex vivo human samples (cells and serum), by using biochemical approaches and correlations with clinical data, describes new biological features of the calcified valve in terms of mitochondrial dysfunctions. In detail, we unveiled a significant deficiency in mitochondrial respiration and in ATP production coupled to increase production of lactates. In addition, mitochondrial population in the pathologic group is aged with significant alterations in biogenesis and mitophagy pathways. We are also reporting an updated view about autophagy accompanying the calcification process and advanced stages of the disease. We provided evidence for a rapamycin-based therapeutic strategy to revert the calcified phenotype to the wild type one. Conclusion: Our data suggest that the CAVS phenotype is featured by defects in mitochondrial quality control mechanisms and that autophagy is not activated enough to counteract cell death and sustain cell functions. Thus, boosting autophagy and mitophagy from short- to long-term reverts quite all pathological phenotypes. Graphical Abstract: